Witt rings of fields of formal power series in two variables - Jaworski, Piotr (Annales Mathematicae Silesianae, 1986)
Let k be any field of characteristic different from 2, F will denote the ring of formal power series in two variables with coefficients from k and K its field of quotients. The aim of the paper is to investigate the structure of the Witt ring of K— W(K). We shall construct certain exact and split sequences of additive homomorphism. We count special the cases of complex and real number fields. The results are also valid for rings of Nash series.